Corrigendum: Morphological Variation of Asian Small Lizards Genus Tytthoscincus Linkem, Diesmos & Brown (Squamata : Scincidae) in Indonesia - Firmansyah, Richo; Riyanto, Awal; Kurniawan, Nia (The Journal of Experimental Life Science, 2023)
CORRIGENDUM.